Sacred philosophy of the seasons: Winter - Duncan, Henry (Edinburgh : William Oliphant and Son ; Glasgow : William Collins ; Dublin : W. Curry & Co. ; London : Hamilton, Adams, & Co., 1837)
This is the fourth volume of four, and contains some notices of Man, him self, as regards his physical, intellectual, and moral powers; and closes with a summary of the argument which this analysis of Nature has exhibited.
Sacred philosophy of the seasons : illustrating the perfections of God in the phenomena of the year / by the Rev. Henry Duncan, D, D, Ruthwell.
Rev Henry Duncan was a Scottish minister and social reformer. He ministered the Ruthwell parish church in Dumfriesshire.
Keywords: rare books, sacred philosophy of the seasons: winter, winter, Henry Duncan